MIGRATION AND CHANGING CONSUMER BEHAVIOUR: A STUDY OF BALASORE DISTRICT IN INDIA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2009)
In an attempt to understand the association between migration and consumer behavior, a primary survey based. on 84 sample households was conducted in Balasore district of Orissa in India. It was well evident from the current study that not only migration was associated with the household article possession diffirential but also by one way or the other it could bring lots of changes in the perception, attitude and behavior of the individuals, related to consumption and marketing.